Water Resources in Nigeria: Rights, Accesibility, Allocation and Management - Negbenebor, Winters O. (Water Nepal, 2003)
The UN Administrative Committee for Co-ordination (UACC) task force on social services states that: ‘at the highest political level there needs to be recognition that water and sanitation are basic needs and rights.’ Similarly, the ministerial declaration of the Hague Conference on Water Security (March 17-22, 2000) also states that water is vital for the life and health of people. We have one goal, it claimed, ‘ensuring that every person has asses to enough water’. Despite such statements, the right of Nigerian people to access to safe water has been persistently violated. Water resources are grossly mismanaged and unequally distributed despite the return of democracy to the country. Local people (especially women, who bear the greater burden of the water crisis) are invariably excluded from decision-making processes involving their water resources. The highly flawed constitution of the Federal Republic of Nigeria, 1999, puts the management and control of water resources beyond the reach of ethnic nationalities and peoples that makes it the exclusive preserve of the federal government of Nigeria. Legislation stipulating how water resources should be managed exists, but it is almost always ignored. This paper uses field analyse, reports and interviews from the oil-rich Niger Delta region as case studies outlining the multifarious problems that bedevil the country as a result of poor water management. The Niger Delta, the most threatened ecosystem in the world, has been degraded by oil multinationals like Shell, Chevron and Mobil. Wetlands and mangroves universally recognised as fragile ecosystems are under stress due to waterlogging and oil pollution. Nigeria recorded 400 oil spills in the first nine months of 2000; these rendered fresh water sources highly polluted. The paper also examines the struggle for self-determination headed by the Movement for the Survival of Ogoni People (MOSOP). It considers sustainable water resource management and fights over resource control between the federal government and the highly impoverished, pauperised and marginalised ethnic nationalities who have organised social movements in the country. It highlights the implications of this situation not only for Nigeria but also for the entire world. Finally, the paper recommends for practical ways of bridging the gap between the government and the people of Nigeria, restoring the people’s right to access to the quantity and quality of water they need, ensuring the equitable allocation of water resources among the Nigerian peoples, and providing for the sustainable management of water resources in the country. Water Nepal Vol.9-10, No.1-2, 2003, pp.349-360